Peningkatan Identitas Visual dan Jangkauan Pasar UMKM Keripik Tempe Boga Rasa melalui Program BRADESPA di Desa Andir - Koswara, Engkos; Nida, Milhatun; Nurbaini Krishna, Nunik; Fitri, Novia; Mustika Dewi, Alya; Nur Khoiriyah, Anazwa; Samrotul Fuadah, Silvi; Fadhlil Arief , Fariz; Lestari, Ayu; Agustian, Renaldi; Cahya Nurfazri, Dicky; Kristianti Hertoni, Yolanda; et al. (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Community Service Program through BRADESPA (Branding, Desain, dan Pemasaran Digital) was implemented to improve the visual identity and marketing reach of the Boga Rasa Tempe Chips MSME in Andir Village, Jatiwangi District. The partners' main challenges included the lack of a logo and tagline, simple packaging without brand identity, and the lack of use of digital platforms for promotion. The program employed a collaborative, participatory approach, including observation, brand identity design (logo, slogan, and packaging), redesign of custom non-transparent pouch packaging, and optimization of digital marketing through business registration on Google Maps. Results demonstrated an improved product professional image, ease of consumer location discovery, and readiness of partners to utilize digital marketing strategies independently. The program provided immediately usable outcomes, although long-term adaptation requires continued support. Future development will focus on social media-based promotion, product certification, and expanding distribution to a wider market.